Not the right time: why parents refuse to let their daughters have the human papillomavirus vaccination. (8th January 2014) - Grandahl, Maria; Oscarsson, Marie; Stenhammar, Christina; Nevéus, Tryggve; Westerling, Ragnar; Tydén, Tanja
Abstract Aim To explore why parents refused to allow their 10‐ to 12‐year‐old daughters to receive the human papillomavirus (HPV) vaccination from the Swedish school‐based vaccination programme. Methods Individual interviews with 25 parents who had been offered, but not consented to, their daughters receiving the HPV vaccination. Results Five themes emerged through the interviews: 1) she is just a little girl, 2) inadequate information, 3) not compatible with our way of life, 4) scepticism about the vaccination and 5) who can you trust? The parents made their decisions with their child's best interests in mind. This was not considered the right time, and the vaccine was perceived as unnecessary and different from other vaccines. Mistrust in Government recommendations and a lack of evidence or information were other reasons to decline. Conclusion The decision‐making process was complex. These parents preferred to wait until their daughter was older and believed the information they received from the school health system was insufficient. The results indicate that a more flexible HPV vaccination schedule may improve vaccine uptake. This includes more transparent information about the virus and the vaccine and information about who to contact to get the daughter vaccinated at a later date.